Effective use of transient vibration damping results for non-destructive measurements of fibre-matrix adhesion of fibre-reinforced flax and carbon composites. (October 2016) - Vanwalleghem, Joachim; De Baere, Ives; Huysman, Sofie; Lapeire, Linsey; Verbeken, Kim; Nila, Alexandru; Vanlanduit, Steve; Loccufier, Mia; Van Paepegem, Wim
Abstract: Fibre-matrix adhesion affects fibre-reinforced composites' mechanical properties, a process which can be improved by applying appropriate sizing on the fibre. Transverse bending tests and Scanning Electron Microscopy (SEM) can help quantify this effect. This paper investigates if modal damping measurements are a reliable alternative for quantifying fibre-matrix adhesion. When a composite sample is vibrating, part of the dissipated energy is due to the internal friction. More internal friction and slipping at the fibre-matrix interface is expected with a weaker fibre-matrix bond, hence increasing the amount of dissipated energy, which in turn is proportional to the modal damping value. This paper researches two different cases to validate this hypothesis. In the first case, we will use two composite samples of flax fibre, one with and one without sizing. In the second case, we will compare flax and carbon fibre laminates. If the only variable is fibre sizing, better adhesion is related to significantly lower damping and higher resonance frequencies. If composite laminates with different fibre and matrix type are compared, lower adhesion is not necessarily related to increased damping and lower resonance frequencies. However, when combining the damping result with SEM microscopy, it is possible to assess the relative contribution to the internal energy dissipation of the fibre, the matrix and the fibre-matrix interface individually.